THE EFFECTIVENESS OF THE EXPERIMENTAL CONTENT OF PHYSICAL EDUCATION IN IMPROVING MORPHOFUNCTIONAL INDEXES OF STUDENTS OF MEDICAL COLLEGE - Kubaj, Grygorij; Iedinak, Genadij; Halamandzhuk, Lesia (Journal of Education, Health and Sport, 2016)
Kubaj G. V., Iedinak G. A., Halamandzhuk L. L. The effectiveness of the experimental content of physical education in improving morphofunctional indexes of students of Medical College. Journal of Education, Health and Sport. 2016;6(9):797-804. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.159347 http://ojs.ukw.edu.pl/index.php/johs/article/view/3903 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 24.09.2016. THE EFFECTIVENESS OF THE EXPERIMENTAL CONTENT OF PHYSICAL EDUCATION IN IMPROVING MORPHOFUNCTIONAL INDEXES OF STUDENTS OF MEDICAL COLLEGE G.V. Kubaj, Prykarpattya National Vasyl Stefanyk University, Ukraine G.A. Iedinak, Lviv State University of Physical Culture, Ukraine L.L. Halamandzhuk, Kamyanets-Podilsky Ivan Ohienko National University, Ukraine Summary. The effectiveness of the content of physical education of students of medical college has been studied for one academic year through their involvement into systematic physical activity. One of the results of resolving this problem was students’ improvement in morphofunctional indexes. The developed organizational and methodological principles were the basis of the proposed content through the involvement of students of medical college for physical activity during physical education classes. Each position included a set of rules that were performed in a certain sequence during the formation of the content of physical education and its implementation in classes. Proposed development has provided 21 girls and 19 boys significantly better results in solving problems within a year than 58 girls and 35 boys who used the content of physical education that was formed and implemented without specified experimental factor. Key words: motivation, physical activity, physical education, students of medical college.